Isotopic composition of the ice cores obtained on the Western Plateau of the Mt Elbrus - A. Kozachek V.; A. Ekaykin A.; V. Mikhalenko N.; V. Lipenkov Ya.; S. Kutuzov S.; А. Козачек В.; А. Екайкин А.; В. Михаленко Н.; В. Липенков Я.; С. Кутузов С. (Ice and Snow, 2015)
The results of the isotopic investigations of several ice cores obtained at the Western Plateau of Mt. Elbrus (the Caucasus) are presented. There is a distinct seasonal cycle in the isotopic composition record in these cores. Mean annual and seasonal values of the isotopic composition and accumulation rate were reconstructed for 89 years (1924–2012). These values were compared with the available regional meteorological data and the atmospheric circulation characteristics. It was shown that in the summer season the isotopic composition reflects the local temperature while in winter it depends on the atmospheric circulation. Представлены результаты изотопных исследований нескольких ледяных кернов, полученных на Западном плато Эльбруса (Кавказ). В изотопном составе кернов прослеживается чёткий сезонный сигнал. Рассчитаны среднегодовые и среднесезонные значения изотопного состава и скорости снегонакопления за 89 лет (с 1924 по 2012 г.). Эти значения сопоставлены с данными метеонаблюдений в регионе и с характеристиками циркуляции атмосферы. Показано, что в тёплый период года изотопный состав зависит от температуры воздуха в регионе, а в холодный – от особенностей циркуляции атмосферы.